Developing Islamic Mall Index based on Maqasid Framework - Alhadi, Muhammad Fajri; Setiawan, Hadi; Zakirullah; Zulfikar (Islamic Marketing Review, 2023)
This research aims to analyze and try to build a maqasid sharia-based mall index. This research uses Simple Additive Weighting (SAW) method to assess the extent to which maqashid syariah index is achieved. The results show that Aeon Mall has a lower weight compared to Cibinong City Mall. The difference in the empowerment index of the two malls lies in the indicators of hifzunnafs, hifzuaql, and hifzubiah. Aeon Mall excels in the hifzuaql indicator, while Cibinong City Mall excels in the hifzunnafs and hifzubiah indicators. Based on the results of this study, it can be concluded that to find out that a mall can be said to be sharia compliant not only seen from one factor, but seen from several Maqasid Syariah indicators. This indexation can be considered in the future for measurements/calculation of the same object.